Assessment of Caring-Based Student Learning Outcomes Using the Nichols Model. - Coffman, Sherrilyn; Espinoza, Nicole (International Journal for Human Caring, 2025)
Assessment of student learning outcomes is an expected measure of institutional effectiveness. Systematic assessment must be completed with meaning and purpose to allow for continuous improvement of a program. As an example of a meaningful assessment process, we will describe how one nursing program utilized the Nichols Model to assess how well students were meeting course and program caring-based outcomes. Preparation for assessment began with the selection of one caring-based program outcome. Assignments and student artifacts from three courses that utilized the outcome were identified. The reviews were conducted by a team of faculty, who assessed and scored student work. The selected outcome was met at an acceptable level in two of the three courses. A report was shared with the faculty, including recommendations for improvement and follow-up. Descriptions of the assessment process will be shared in quality improvement and accreditation reports.